MORAL VALUE IN NOVELLASKAR PELANGIAND PADANG BULAN BY ANDREA HIRATA - Rukiyah, Siti; Emzir, Emzir; Ridwan, Sakura (IJLECR (International Journal of Language Education and Cultural Review), 2017)
Thisreserachaimsto gain a deep understanding of the moral values â€‹â€‹contained in the novel Laskar Pelangi and Padang Bulan by Andrea Hirata with the study of genetic structuralism. This research uses qualitative approach with content analysis technique. The data in this researcth is words, sentences, in the form of phrases, description of characters and dialogue of figures and dialogues among the characters that indicate the existence of moral values â€‹â€‹in the novel. Based on the result of the research indicate that novel Laskar Pelangi and Padang Bulan by Andrea Hirata have moral value in the form of: a) the relationship of human being with God, b) the relationship of human being with themselves, that is self awareness about obligation on themselves, c) the relationship of human beingwith human being in the social atmosphere, ie one’s consciousness towards himself and the social sphere and d) the relationship of human being with the nature. Moral values â€‹â€‹in terms of the author’s world view in the novel include a) the relationship of human being with the God, b) the relationship of human being with themselves, c) the relationship of human beingwith human being in thesocialatmosphere, and d) therelationship of human beingwiththenature.